2019
DOI: 10.1063/1.5089877
|View full text |Cite
|
Sign up to set email alerts
|

Powering the 21st century by wind energy—Options, facts, figures

Abstract: This review article aims to provide an overview and insight into the most relevant aspects of wind energy development and current state-of-the-art. The industry is in a very mature stage, so it seems to be the right time to take stock of the relevant areas of wind energy use for power generation. For this review, the authors considered the essential aspects of the development of wind energy technology: research, modeling, and prediction of wind speed as an energy source, the technology development of the plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 299 publications
0
38
0
Order By: Relevance
“…Local wind systems like the Mistral, the Bora, and the flow through the Strait of Gibraltar (Levante and Poniente) are clearly visible. Due to the limited resolution, some of these flows are not fully resolved in commonly used reanalysis datasets like ERA5 (Hersbach and Dick, 2016) and CFSRv2 (Saha et al, 2014) or MERRA2 (Gelaro et al, 2017) (not shown here). The inset figures in Fig.…”
Section: Adjustments To Wrf-wasp Downscaling Used For Evaluation Agaimentioning
confidence: 95%
“…Local wind systems like the Mistral, the Bora, and the flow through the Strait of Gibraltar (Levante and Poniente) are clearly visible. Due to the limited resolution, some of these flows are not fully resolved in commonly used reanalysis datasets like ERA5 (Hersbach and Dick, 2016) and CFSRv2 (Saha et al, 2014) or MERRA2 (Gelaro et al, 2017) (not shown here). The inset figures in Fig.…”
Section: Adjustments To Wrf-wasp Downscaling Used For Evaluation Agaimentioning
confidence: 95%
“…The importance of wind energy in the energy supply of the future will increase in coming years while costs for WTs steadily fall [1]. One driver for WT costs is the reliability.…”
Section: Motivationmentioning
confidence: 99%
“…Wind turbine technology converged in the mid-1980's to a dominant three-blade and horizontal axis design [75]. Since then, new turbine technology has largely been characterized by improved efficiencies through increased turbine hub height and larger rotor diameters, enabling plants to access higher sustained winds more efficiently [76]. Figure 7 displays growing tower heights and cost reductions since the early 1980's.…”
Section: Research and Developmentmentioning
confidence: 99%